CRITERIA FOR DIAGNOSING AND ASSESSING COMMON RISK FACTORS FOR ACUTE ABDOMINAL DISEASES ASSOCIATED WITH COVID-19 AND POST-COVID SYNDROME (Conferencea, 2024)
This indicates that taking into account the unfavourable epidemiological situation associated with COVID-19 infection, an international registry was created dedicated to "Analysis of the dynamics of comorbid diseases in patients with SARS-COV2 (ACTIV SARS-COV-2) infection". This registry studied the impact of specific risk factors (obesity, smoking, arterial hypertension, old age) and chronic infectious diseases on the risk of developing severe and fatal consequences. This international registry once again confirms the importance of a comprehensive clinical and epidemiological study of chronic non-communicable diseases, including acute diseases of the abdominal cavity (AIDs), and on this basis, the need to develop models of their regional prevention in the Uzbek population with COVID-19.